The secret history of Audrey James : a novel [large type] - Marshall, Heather (Heather J.) (Center Point Large Print, 2025)
"Northern England, 2010. After a tragic accident upends her life, Kate Mercer leaves London to work at an old guest house near the Scottish border, where she hopes to find a fresh start and heal from her loss. When she arrives, she begins to unravel the truth about her past, but discovers that the mysterious elderly proprietor is harboring secrets of her own. Berlin, 1938. Audrey James is weeks away from graduating from a prestigious music school in Berlin, where she's been living with her best friend, Ilse Kaplan. As war looms, Ilse's family disappears and high-ranking Nazi officers confiscate the house. In desperation, Audrey becomes their housekeeper while Ilse is forced into hiding in the attic. When a shocking turn of events embroils Audrey in the anti-Hitler movement, she must decide what matters most: protecting those she loves, or sacrificing everything for the greater good."--